[Royal Palms, Port of Spain, Trinidad, B.W.I.] - (:unkn) unknown (My University, 2010)
This postcard shows a car driving down a avenue lined with stately palms. This photograph may have been taken in St. Clair, a suburb of Port of Spain, just around the time of the First World War.
Colour: Sepia; Style: Portrait; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Palms--Trinidad and Tobago; Dwellings--Trinidad and Tobago; Streets--Trinidad and Tobago; Automobiles--Trinidad and Tobago; Roads--Trinidad and Tobago; Streets--Trinidad and Tobago; [1920]; Cities and towns--Trinidad and Tobago--Port of Spain; Fences--Trinidad and Tobago; Pavements--Trinidad and Tobago; Transportation--Trinidad and Tobago